The Evaluation of Authentic Assessment Implementation in the Kurikulum 2013 at SD Negeri 067690 Medan - Deli Kesuma; Edy Surya; Edi Syahputra (BIRCU, 2019)
Assessment certainly has challenges and problems, especially for teachers who directly implement the applicable curriculum. Therefore, this study aims to find out the extent of the implementation of authentic assessment models in kurikulum2013 which viewed from aspects of readiness, planning, and implementation of assessments conducted by teachers. This type of research is an evaluative descriptive study with quantitative approach. The study is conducted at SD Negeri 067690 Medan with total sample of 13 teachers. The results of this study indicate that the implementation of authentic assessment model in thekurikulum 2013at SD Negeri 067690 Medan, as follows: the percentage of evaluations to the readiness assessment shows good results with an average of 79.75%, the percentage of evaluations of the assessment plan shows good results with an average of 77.43%, and the percentage of evaluations of the implementation of the assessment shows good results with an average of 66.23%. Based on these results, it can be concluded that the implementation of authentic assessment model in the kurikulum 2013at SD Negeri067690 Medan is unfavorable category. In line with implementation of the curriculum 2013.